Integrated Strategy of Network Pharmacological Prediction and Experimental Validation Elucidate Possible Mechanism of Bu-Yang Herbs in Treating Postmenopausal Osteoporosis via ESR1 - Xia, Hanting; Liu, Jiangyuan; Yang, Wenlong; Liu, Min; Luo, Yunfeng; Yang, Zhijun; Xie, Jingbo; Zeng, Huiliang; Xu, Rui; Ling, Houfu; Zeng, Qinghe; Xu, Huihui; et al. (Frontiers in Pharmacology, 2021)
Postmenopausal osteoporosis (PMOP) is a kind of bone metabolism disease related to estrogen deficiency with an increasing incidence. Traditional Chinese (TCM) has long been used and showed effective in treating PMOP. In the current study, Bu-Yang herbs were found to be the most frequently used and efficient TCM herbs in PMOP treatment. However, the chemical and pharmacological profiles were not elucidated. Network pharmacology was conduceted on representative Bu-Yang herbs (Yin-Yang-Huo, Du-Zhong, Bu-Gu-Zhi, Tu-Si-Zi) to investigate the mechanism of Bu-Yang herbs on PMOP. Chemical compounds, potential targets and disease related genes were obtained from corresponding database. Results showed that Bu-Yang herbs could interact with ESR1 and estrogen signaling pathway. For further validation, Bu-Yang decoction (BYD), formula consisted by above-mentioned 4 Bu-Yang herbs were introduced for experimental validation. In vivo, BYD significantly reversed ovariectomy (OVX)-induced osteoporosis progress in a dose-dependant manner by up-regulation of bone mineral density and amelioration of bone micro architecture. In vitro, BYD significantly improved the proliferation and mineral nodules formation of osteoblasts. Both in vitro and in vivo results illustrated that the phenotype change induced by BYD is correlated with up-regulated of ESR1 and activation of β-catenin pathway. Meanwhile, inhibition of ESR1 by ICI182, 780 blocked the osteogenic phenotype and β-catenin pathway activation induced by BYD. In conclusion, the current study suggested that Bu-Yang herbs are most useful TCM herbs in treating PMOP. Furthermore, the integrated strategy of network pharmacology prediction with experimental validation suggested that BYD exerted its anti-PMOP via ESR1 and the downstream mechanism might be activation of β-catenin signaling pathway.